2011
DOI: 10.1007/s00268-010-0935-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the Gastric Cardia is Rising in Incidence in an Asian Population and is Associated with Adverse Outcome

Abstract: Similar to western societies, the incidence of proximal gastric cancer is increasing in Singapore. Cardia tumors are associated with poorer outcomes, suggesting that cardia cancer is a distinct disease from true gastric cancer requiring different management strategies to improve the outcome for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 39 publications
(44 reference statements)
7
92
0
2
Order By: Relevance
“…Recent studies indicate that the incidence rate of gastric cardia cancer is as high as esophageal cancer in the high-incidence area of esophageal cancer. Epidemiological studies also have reported an increasing incidence of gastric cardia cancer in some Asian countries during the past few decades (Blaser et al, 2002;Tony et al, 2007;Kusano et al, 2008;Zhou et al, 2008;Deans et al, 2011), owning to the development of the early diagnosis of gastric cardia cancer and its clear definition. Screening program of esophageal and gastric cardia cancer screening of Linzhou in [2005][2006] has proofed it and has also showed the rise of the ratio of esophageal to gastric cardia cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that the incidence rate of gastric cardia cancer is as high as esophageal cancer in the high-incidence area of esophageal cancer. Epidemiological studies also have reported an increasing incidence of gastric cardia cancer in some Asian countries during the past few decades (Blaser et al, 2002;Tony et al, 2007;Kusano et al, 2008;Zhou et al, 2008;Deans et al, 2011), owning to the development of the early diagnosis of gastric cardia cancer and its clear definition. Screening program of esophageal and gastric cardia cancer screening of Linzhou in [2005][2006] has proofed it and has also showed the rise of the ratio of esophageal to gastric cardia cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Data from prior Asian studies have been inconsistent with regard to the incidence of GCA. Some showed an increase in incidence in Japanese, Chinese, Korean, Singaporean and South Indian populations while others showed no change [19][20][21][22][23][24]. A metaanalysis by Corley et al showed that there was no clear association between GCA and obesity in the Asian population and one study had even showed negative correlation [15,25].…”
Section: What Does the Current Study Add?mentioning
confidence: 99%
“…In contrast, the incidence of AEGJ is unchanged or only gradually increasing in the East [5][6][7], and its clinicopathological features have not yet been elucidated, especially in advanced, nonresectable tumors.…”
Section: Introductionmentioning
confidence: 96%